Therapeutic interventions to reduce the risk of progression from prediabetes to type 2 diabetes mellitus - Mclellan, Katia Cristina Portero [UNESP]; Wyne, Kathleen; Villagomez, Evangelina Trejo; Hsueh, Willa A. (Dove Medical Press Ltd, 2014)
Clinical trials have demonstrated that it is possible to prevent diabetes through lifestyle modification, pharmacological intervention, and surgery. This review aims to summarize the effectiveness of these various therapeutic interventions in reducing the risk of progression of prediabetes to diabetes, and address the challenges to implement a diabetes prevention program at a community level. Strategies focusing on intensive lifestyle changes are not only efficient but cost-effective and/or cost-saving. Indeed, lifestyle intervention in people at high risk for type 2 diabetes mellitus (T2DM) has been successful in achieving sustained behavioral changes and a reduction in diabetes incidence even after the counseling is stopped. Although prediabetes is associated with health and economic burdens, it has not been adequately addressed by interventions or regulatory agencies in terms of prevention or disease management. Lifestyle intervention strategies to prevent T2DM should be distinct for different populations around the globe and should emphasize sex, age, ethnicity, and cultural and geographical considerations to be feasible and to promote better compliance. The translation of diabetes prevention research at a population level, especially finding the most effective methods of preventing T2DM in various societies and cultural settings remains challenging, but must be accomplished to stop this worldwide epidemic.
Keywords: lifestyle; T2DM; intervention; prevention